Genetic relatedness of commensal strains of Candida albicans carried in the oral cavity of patients' dental prosthesis users in Brazil - Pires-Goncalves, Regina Helena; Miranda, Elaine Toscano; Baeza, Lilian Cristiane; Matsumoto, Marcelo Teruyuki; Zaia, Jose Eduardo; Mendes-Giannini, Maria José Soares [UNESP] (Springer, 2007)
The aim of this study is to describe the degree of yeast-colonization in diabetic and hemodialysed-users of dental prostheses. Individuals (306) were examined using an oral rinse technique in order to evaluate the incidence of yeast-carriage, and genotype of C. albicans. Yeasts were isolated from 68.4% (91/133) individual's dental prostheses users. Dental prostheses were found to be a significant factor for the yeast colonization (P < 0.05). Overall, the intensity of carriage was higher in diabetic patients as compared with health and hemodialysed individuals (P < 0.05). The isolation rates were: C. albicans (51.7%), C. parapsilosis (20.9%), C. tropicalis (14.3%), C. glabrata (6.6%), C. krusei (3.3%), C. rugosa (1.1%), and Pichia (Pichia ohmeri, 2.2%). Ready-To-Go RAPD Analysis Beads were used and primer OPJ 6 distinguished the C. albicans isolates found in prostheses users. All the isolates were grouped into 11 RAPD profiles in four main clusters and, the average S (AB) for the entire collection of 47 C. albicans isolates were 0.779 +/- 0.178. Over 85% of isolates had a similarity level higher than or equal to 0.8 reinforcing the idea that the use of dental prostheses, independently of the host's clinical condition, probably provides the necessary conditions for these strains to gain a growth-specific advantage over others.
Keywords: oral Candida species; Randomly amplified polymorphic DNA (RAPD); C. albicans genotype; dental prostheses; oral carriage